Arabic, grammar and teaching: an Islamic historical perspective - Selim, Nadia (Penerbit Universiti Kebangsaan Malaysia, 2018)
Motivated by the need to rethink Islamic education and Arabic teaching in Western Islamic schools (Ramadan 2004), this article seeks to present an analytical exploration of Islamic educational thought on the purpose of Arabic grammar and its place in Arabic language teaching. The article will review the rise of Arabic grammar and thought surrounding its instruction to understand whether one of the most prevalent approaches to teaching Muslim children Arabic as a foreign or second language today, the Grammar-Translation Method (GTM), is part of the Islamic educational tradition. The GTM, which is not suited to the promotion of childhood literacy or language acquisition and leaves many children disengaged and with stilted rudimentary literacy, is often conflated with the rich philological tradition of the Islamic civilization. However, was nahw [grammar] meant to be the core component of Muslim childhood learning experiences in the way that it is today, or has the GTM method supplanted Islamic civilizational thought on teaching language? This article seeks to answer this question and will do so by reviewing the purpose of the Arabic language in the Islamic civilization, the rise of Arabic grammar and thought surrounding education and Arabic instruction.